EFEK KOMUNIKASI PIMPINAN ORGANISASI GERAKAN PEMUDA ANSOR PAC PESANGGARAN KABUPATEN BANYUWANGI - Abdul Aziz; Moh. Ansori (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2022)
Community or organization is a form of cooperation between several people to achieve a goal by holding divisions and work regulations. This research is motivated by the fact that every organization in random also has its own character or culture. Likewise with the Ansor Youth Movement Organization for the Pesanggaran District Children's Management Branch. This study examines the effects of communication on the organization of the Ansor Youth Movement for the Sub-District of Pesanggaran Sub-District. This type of research uses qualitative methods using data from observations and interviews with informants. The informants in this study were 5 people with the criteria that they had been registered as official members of the Ansor Youth Movement Organization, Pesanggaran Sub-District Branch Management. The result is that the organization that was established under the NU Banom has the aim of strengthening kinship ties with routine activities that are held every two weeks, once a month and a year.